Analysis of Edu-Smart Learning Management System Software - Agus Herlambang, Bambang; ., Muhtarom; Saifuddin Zuhri, Muhammad (KnE Social Sciences, 2022)
Edu Smart is a learning management system software (LMS) that was built as one of the distance learning solutions during the COVID-19 pandemic and became a resource for learning activities and administration activities. This research aims to measure the quality of Edu Smart LMS related to operational products used by the McCall method. The analysis is carried out on aspects of product operation consisting of the quality factors of correctness, reliability, efficiency, integrity, and usability. The data was collected through questionnaires from 28 respondents consisting of teachers, students, and UPT ICT staff of Universitas PGRI Semarang. The results showed that the overall quality of Edu Smart LMS is at the level of 52.6% (the quality of LMS Edu Smart is quite good). Several recommendations were given for the improvement and development of LMS Edu Smart, among others related to the addition of features, security, and ease of access. Keywords: Learning management system; Edu-Smart; Mc. Call method.